Study of the Spectroscopic Data Analysis Pretreatments for Enhancing Performance of NIR Calibration Model for Determining the Brix Value of Japanese Pear - Sakulnarmrat, Karunrat; Jannok, Piyamart (Naresuan University Journal: Science and Technology (NUJST), 2017)
Spectral pretreatment is one of essential procedures to improve data quality prior to establishment of calibration model and removal of physical interferences from spectra, which could enhance the model accuracy. An evaluation of Japanese Pear ( Pyrus pyrifolia ) sweetness using Near Infrared (NIR) spectroscopy technique with short wavelength (700 ~ 1100 nm) region and interactance mode was investigated.  Several multivariate calibration techniques were compared and validated by establishing figures of merit. Various pretreatments with truncation were also employed in order to construct the best model of sweetness assessment. This included an individual and combination pretreatments. The best calibration was obtained through combination of multiplicative scatter correction (MSC) and second derivative (MSC+2D). It was characterized as follows: (F = 3), R 2 = 0.77, SEC = 0.56°Brix, SEP = 0.64°Brix and bias of -0.10°Brix. The results suggest potential application of NIR technique by food industries to assess pear sweetness that is non-destructive, fast and flexible. Keywords : Pear, Near infrared spectroscopy, spectroscopic data analysis, spectral pretreatment
Keywords: Pear, Near infrared spectroscopy, spectroscopic data analysis, spectral pretreatment